PENGARUH KEPUASAN DAN KEPERCAYAAN TERHADAP LOYALITAS NASABAH DENGAN MEDIASI SWITCHING BARRIERS (Studi Pada Debitur di PD. BKK Dempet Kabupaten Demak Cabang Guntur) (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aimed to analyze the effect of satisfaction on customer loyalty and trust with the mediation of switching barriers (studies on the debtor in PD. BKK Dempet Demak Guntur Branch). The research sample of 100 respondents, the sampling technique using purposive sampling is a method of sampling to establish predetermined criteria include: (1) customer PD. BKK Dempet Guntur Branch Demak ever apply for credit, (2) at least 17 years of age; (3) willing to be the respondent. The results show that there are positive influence between satisfaction with the switching barrier, there is a positive influence between confidence in the switching barrier, there is a positive effect of satisfaction on customer loyalty, there is a positive effect of trust on customer loyalty, there are positive influence between switching barrier on customer loyalty. Other results indicate switching barrier does not mediate the effect of satisfaction on customer loyalty and switching barrier does not mediate the effect of trust on customer loyalty Keywords : satisfaction and trust on customer loyalty with mediation switching barriers.